Subscapularis Repair During Reverse Total Shoulder Arthroplasty Using a Stem-Based Double-Row Repair: Sonographic and Clinical Outcomes. Issue 3 (9th March 2020) - Erickson, Brandon J.; Shishani, Yousef; Bishop, Meghan E.; Patel, Midhat; Jones, Stacy; Romeo, Anthony A.; Lederman, Evan S.; Gobezie, Reuben
Background: Treatment of the subscapularis in reverse total shoulder arthroplasty (RTSA) is a controversial topic, with conflicting evidence regarding outcomes after repair. Purpose/Hypothesis: The purpose of this study was to report clinical and sonographic outcomes of a through-implant double-row suture technique for subscapularis repair in RTSA and to compare clinical outcomes and range of motion (ROM) between patients with an intact subscapularis tendon repair versus those whose tendon repair was not intact. The authors hypothesized that the novel repair technique would find more than 80% of tendons intact on ultrasound, with significant improvement in clinical outcome scores and ROM. The authors also hypothesized that patients with an intact subscapularis tendon repair would have better clinical outcomes compared with those with a nonintact tendon repair. Study Design: Case series; Level of evidence, 4. Methods: The study included all patients who underwent RTSA by 1 of 2 surgeons between August 2016 and March 2017 with the through-implant double-row suture technique for subscapularis repair. Subscapularis tendon integrity was assessed postoperatively via ultrasound at minimum 1-year follow-up. American Shoulder and Elbow Surgeons (ASES), Single Assessment Numeric Evaluation (SANE), and pain visual analog scale (VAS) scores were recorded at the final follow-up visit in addition to ROM measures. Results: A total of 48 patients (31 males, 17 females; mean age, 68.9 ± 7.4 years; mean follow-up, 13.8 ± 2.1 months) were included. On ultrasound, the subscapularis was intact in 83.3% of patients. Regarding preoperative versus postoperative outcome scores, the ASES score (mean ± SD) significantly improved from 38.3 ± 14.7 to 81.9 ± 13.6, the SANE score significantly improved from 29.8 ± 24.2 to 75.5 ± 21.0, and the VAS pain score significantly improved from 5.9 ± 2.1 to 1.2 ± 1.6 ( P < .001 for all). Forward flexion and external rotation significantly improved. No significant difference existed in clinical outcome scores or ROM between patients with intact versus torn subscapularis tendons based on ultrasound. Conclusion: Subscapularis repair using a stem-based double-row repair technique during RTSA demonstrated an overall healing rate of 83.3%, as evidenced by ultrasound examination at short-term follow-up. Integrity of subscapularis repair did not affect clinical outcome or ROM.